IMPLEMENTASI SIMULASI MENGAJAR DALAM PENGEMBANGAN STRATEGI PEMBELAJARAN INOVATIF PADA PENDIDIKAN PANCASILA DI KELAS IV SD NEGERI KURIPAN - Nur Rohimah; Susilo Tri Widodo; Arina Faizatun Nikmah; Indah Dewi Setiyowati (STKIP Subang, 2025)
This research discusses the problems of Pancasila Education learning in class IV of Kuripan State Elementary School, which is still dominated by conventional methods, limited use of media, and low student involvement. The purpose of this research is to describe the implementation of teaching simulations in the development of innovative learning strategies and to analyse their contribution to improving the quality of learning. This research uses a descriptive qualitative approach with the subjects being fourth-grade teachers and students. Data was collected through observation, interviews, and documentation, then analysed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that teaching simulations enable teachers to design more interactive lessons and utilise technology-based media. The use of Wordwall during the simulation created a more engaging learning atmosphere and encouraged students to actively participate through educational game activities. Students showed increased motivation, courage to ask questions, and participation in answering and discussions. Teachers also gained new insights into more varied and student-centered teaching strategies. Overall, the implementation of teaching simulations contributes positively to the development of innovative learning strategies and provides a more meaningful learning experience for students.